Alpinia japonica extract induces apoptosis of hepatocellular carcinoma cells through G0/G1 cell cycle arrest and activation of JNK : AJ induces apoptosis of HCC - Kim, Jae-Goo; Kim, Wooki; Kim, Ki-Young (Cellular and Molecular Biology, 2023)
Hepatic cancer was the third most prevalent cause of cancer-related death worldwide in 2018, and its incidence is increasing. While therapeutic agents for hepatic cancer have improved, these agents can cause serious side effects, including damage to healthy tissues. To overcome this limitation, more than 3,000 plants have been used globally as common alternatives for cancer treatment. The anti-cancer activity of Alpinia japonica, one of the traditional herbal medicines (Korean name: Kkot-yang-ha), was investigated. Water extract of A. japonica (AJ) decreased the cell viability of hepatic cancer cells. AJ extract showed greater than 70% loss of mitochondrial potential in HepG2 cells as demonstrated by JC-1 staining. Apoptosis was induced by treatment with AJ extract as shown through FACS analysis, and G0/G1 phase arrest of 76.66% HepG2 cells was confirmed through cell cycle analysis and quantitative RT-PCR. Improper regulation of ERK1/2 might contribute to cell death, and JNK activation is necessary for apoptosis induced by stress stimuli. AJ extract stimulated the phosphorylation of JNK and ERK1/2, mitogen-activated protein kinases (MAPKs), in HepG2 cells. AJ extract has anticancer activity by inhibiting cell cycle progression, leading to apoptosis of hepatic cancer cells. This extract could potentially be used as a therapeutic agent for hepatic cancer.